Frugality, brand attitude and purchasing behavior in green restaurants in emerging Latin American markets - Villavicencio, María Fernanda; Schlesinger, Walesska (Revista de Ciencias Sociales, 2023)
Frugality has often been associated with resource-saving behavior that contributes to sustainable consumption. The study presented here aims to investigate consumer frugality and its relationship with brand attitude, purchase intention and purchase behavior in ecological foodservice in an emerging market in Ecuador. A non-experimental quantitative study was conducted with a sample of 327 customers residing in Ecuador of an ecological cafeteria considered an icon brand in the country. The conceptual model proposed empirically demonstrates the negative effect on the relationship between frugality and green purchasing behavior and the mediating role of purchase intention and brand attitude in this relationship; it was also shown that the relationship between brand attitude and green purchasing behavior is mediated by purchase intention. The results suggest that green marketing strategies in emerging markets should take into account consumer beliefs and values as they have an impact on purchase behavior. The article includes a theoretical model that yields relevant implications for managers involved in green services and offers practical guidelines for understanding consumer behavior to aid effective green marketing management in foodservice operations.